Changes in taste perception in elderly population and its potential impact on oral health: a systematic review with meta-analysis - Larisse Santos Mendonça Alves; Júlia Maria de Sousa Munduri; Mariana Caldas de Oliveira Mattos; Cristine Miron Stefani; Naile Dame-Teixeira (Frontiers in Oral Health)
AimGustatory function plays a fundamental role in various aspects related to nutrition and health, and the decline in taste perception can result in a series of adverse consequences. This is expected with aging due to a decrease in taste buds and other conditions, leading to systemic and oral diseases. We aimed to compare taste sensitivity in the elderly population vs. adults.MethodsThis systematic review was reported according to PRISMA guidelines. The search was performed in four databases, as well as in grey literature. The risk of bias was assessed using the JBI's critical appraisal tools for observational studies. A meta-analysis with subgroups according to each flavor was conducted to obtain differences in means for adults vs. elderly (random-effects model).ResultsOut of the 5,660 studies retrieved, 18 observational studies were included, representing a total of 1,680 aged 18–59 years and 1,048 aged ≥ 60 years. Elderly individuals need higher concentrations to distinguish flavors compared to adults. In a qualitative analysis, all flavors showed differences between the groups, with sweet flavor being the easiest to recognize and the thresholds between the groups not being highly discrepant. However, in the meta-analysis, statistical differences were observed for sweet, salty, and umami flavors, while there were no statistical differences for sour and bitter flavors between the groups.ConclusionsThere are significant differences for distinguishing sweet, salty, and umami flavors between adults and elderly. Bitter and sour flavors did not exhibit differences in elderly.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?RecordID=463873, PROSPERO (CRD42023463873).